An energy based method for seismic design of frame structures equipped with metallic yielding dampers considering uniform inter-story drift concept. (15th February 2020) - Aliakbari, Fatemeh; Garivani, Sadegh; Aghakouchak, Ali Akbar
Highlights: An energy-based method is proposed for seismic design of the building structures equipped with metallic yielding dampers. A step-by-step design flowchart is presented. Equations are developed to determine the required number of dampers in stories. Vertical distribution of energy in multi-story structures is obtained and compared with that of shear force. The spectrum of input energy normalized with respect to mass of structure is extracted based on the results of nonlinear dynamic analysis of multi-story structures. Abstract: Application of passive control systems in earthquake-resistant structures has attracted much attention in recent decades. One of the most important obstacles to the widespread use of these systems is the lack of simple methods for analysis and design of these systems. Energy based approach is one of design methods that has been considered extensively in recent years. In this paper, an energy-based method is proposed for seismic design of the building structures equipped with metallic yielding dampers. Considering the concepts of energy balance in the structure, the required equations to determine the number of dampers in each story are developed so that uniform drift and ductility demands are achieved in different stories. A step-by-step design flowchart is presented, and then several building structures are designed using a computer code written based on it. To check efficiency of the method, seismic responses of designed structures are evaluated under two sets of artificial and real records using dynamic analysis of the FE models. The responses are compared with the assumptions and objectives of the proposed design method. The results indicate a good agreement and it is concluded that the proposed method can be successfully used to design building structures equipped with metallic yielding dampers.